Long-Term Storage Does Not Affect the Expression Profiles of mRNA and Long Non-Coding RNA in Vitrified-Warmed Human Embryos - Li, Jingyu; Zhu, Ling; Huang, Jin; Liu, Weiwei; Han, Wei; Huang, Guoning (Frontiers in Genetics, 2022)
Although vitrification has been widely applied in assisted reproductive technology, it is unknown whether storage time has any impact on the mRNA and lncRNA expression profiles in human embryos. Eleven women (aged 23-35 years) who had undergone IVF treatment were recruited for this study. The transcriptomes of 3 fresh eight-cell embryos and 8 surviving vitrified-warmed eight-cell embryos (4 embryos were cryostored for 3 years, and the others were cryostored for 8 years) were analyzed through single-cell RNA-Seq. No differentially expressed mRNAs or lncRNAs were identified between the 3-year group and 8-year group. A total of 128 mRNAs and 365 lncRNAs were differentially expressed in the 8 vitrified-warmed embryos compared with the fresh embryos. The vitrification-warming impact was moderate, and it was mainly related to the pathways of metabolism, stress response, apoptosis, cell cycle, cell adhesion, and signaling for TFG-β and Hippo. The analysis of target mRNAs suggested that lncRNAs might contribute to the regulation of mRNAs after vitrification-warming. Our findings indicated that the effects of vitrification-warming on the mRNA and lncRNA expression profiles in human embryos, which may be induced by the vitrification and warming procedures, this suggested that long-term cryostorage of human embryos is safe.